Spatio-temporal assessment of integrating intermittent electricity in the EU and Western Balkans power sector under ambitious CO2 emission policies. (1st December 2018) - Mesfun, Sennai; Leduc, Sylvain; Patrizio, Piera; Wetterlund, Elisabeth; Mendoza-Ponce, Alma; Lammens, Tijs; Staritsky, Igor; Elbersen, Berien; Lundgren, Joakim; Kraxner, Florian
Abstract: This work investigates a power dispatch system that aims to supply the power demand of the EU and Western Balkans (EUWB) based on low-carbon generation units, enabled by the expansion of biomass, solar, and wind based electricity. A spatially explicit techno-economic optimization tool simulates the EUWB power sector to explore the dispatch of new renewable electricity capacity on a EUWB scale, under ambitious CO2 emission policies. The results show that utility-scale deployment of renewable electricity is feasible and can contribute about 9–39% of the total generation mix, for a carbon price range of 0–200 €/tCO2 and with the existing capacities of the cross-border transmission network. Even without any explicit carbon incentive (carbon price of 0 €/tCO2 ), more than 35% of the variable power in the most ambitious CO2 mitigation scenario (carbon price of 200 €/tCO2 ) would be economically feasible to deploy. Spatial assessment of bio-electricity potential (based on forest and agriculture feedstock) showed limited presence in the optimal generation mix (0–6%), marginalizing its effect as baseload. Expansion of the existing cross-border transmission capacities helps even out the variability of solar and wind technologies, but may also result in lower installed RE capacity in favor of state-of-the-art natural gas with relatively low sensitivity to increasing carbon taxes. A sensitivity analysis of the investment cost, even under a low-investment scenario and at the high end of the CO2 price range, showed natural gas remains at around 11% of the total generation, emphasizing how costly it would be to achieve the final percentages toward a 100% renewable system. Highlights: A case study on decarbonizing the EU and Western Balkans power sector is performed. As cost of variable renewables drops, decarbonization proceed regardless of CO2 policies. Sensitivity analysis about the impact of cross-border transmission capacity expansion. Final percentages toward a 100% renewable electricity likely to be costly to achieve.